2015
DOI: 10.1021/acscatal.5b00840
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Electrochemical Reduction of CO2 to CO on Nanostructured Ag Surfaces

Abstract: Electroreduction of CO2 in a highly selective and efficient manner is a crucial step towards CO2 utilization. Nanostructured Ag catalysts have been found to be effective candidates for CO2 to CO conversion. In this report, we combine experimental and computational efforts to explore the electrocatalytic reaction mechanism of CO2 reduction on nanostructured Ag catalyst surfaces in an aqueous electrolyte. In contrast to bulk Ag catalysts, both nanoparticle and nanoporous Ag catalysts show enhanced ability to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
526
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(553 citation statements)
references
References 33 publications
25
526
1
1
Order By: Relevance
“…2) is the rate-determining, followed by another electron transfer. 51,53,54 The effects of halides present at the electrode surface or in the electrolyte have been previously reported for CO 2 electroreduction on copper surfaces 55 , and substantial improvement in current efficiency and selectivity was observed. It appears that the presence of chloride ions on the Ag electrode surface or in the electrolyte solution in proximity to the electrode promotes selectivity and activity for the CO 2 reduction reaction.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…2) is the rate-determining, followed by another electron transfer. 51,53,54 The effects of halides present at the electrode surface or in the electrolyte have been previously reported for CO 2 electroreduction on copper surfaces 55 , and substantial improvement in current efficiency and selectivity was observed. It appears that the presence of chloride ions on the Ag electrode surface or in the electrolyte solution in proximity to the electrode promotes selectivity and activity for the CO 2 reduction reaction.…”
Section: Resultsmentioning
confidence: 70%
“…52 Under experimental conditions similar to those described in this work, HCO 3 − is the most likely source of protons, since the pK a of bicarbonate is much lower as compared to that of water. 51 The step (3) is an electrochemical step coupled to a chemical reaction involving proton and electron transfer, and the step (4) is the desorption of CO product. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 As shown in Figure 4, the polycrystalline Ag foil exhibited a Tafel slope of 137 mV dec −1 , which is close to 140 mV dec −1 for polycrystalline Ag under similar experimental conditions, 24 and comparable to 132 mV dec −1 measured in 0.5 M KHCO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Thes pecific activity for CO production declines by about 15 %upon increasing the rotation rate from 700 to 3500 rpm (Figure 4b). While we cannot rule out several competing effects, [25] we note that the local activity of K + and CO 3 2À must rise in tandem with elevated local pH, and that these species may serve to promote CO production in this system. These results are also in contrast to observations on Au electrodes,f or which the rate of CO production is largely independent of the electrode rotation rate.…”
Section: Angewandte Chemiementioning
confidence: 77%
“…Studies on tin 5,6 and indium 7,8 have demonstrated the importance of a hydrated oxide layer, either native or anodized, which can interact with CO 2 to form a surface-bound carbonate species that is implicated as an essential intermediate. Other research has shown that a size-dependence exists on gold, 9,10 palladium, 11 silver, 10,12,13 and tin oxide 14 nanoparticles for the conversion of CO 2 , with an optimum diameter less than 10 nm but typically greater than 2 nm. Such nanoparticles have a high proportions of edge and corner sites, which, because of their lower * Electrochemical Society Student Member.…”
mentioning
confidence: 98%